PROBLEMS OF BIOSAFETY IN CURRENT INTERNATIONAL LAW - Gulyaeva, Elena Evgenyevna (Revista Direitos Culturais, 2025)
The author seeks to understand the content and legal concept of biosafety in International Law. The researcher seeks to list the biosafety issues in order to define concrete aspects related to responsibility of the States for using biological weapons. The author analyzes new legal trends on ensuring the international biosafety. The article is focused on legal issues by raising many questions about what should be considered a just war in the view of international humanitarian law, the issues of fundamental principles in current international law (the principle use of force, the right of States to self-defense in case of a bioattack, the principle of the peaceful settlement of international disputes, the principle of non-interference in the internal affairs of States, arms control, and responsibility). The writer gives an overview of new types of sovereignty such as biosovereignty, cyber sovereignty, and genomic sovereignty of States, the legal concept of international biocrimes (genomocide), the legal classification of bioterrorism, bioaggression, biopolitics, and bioeconomics. The author considers the importance of facilitating the broad interpretation of the concept of biosafety. The research uses general scientific and special cognitive techniques wherein legal analysis and synthesis, systemic, formal-legal, comparative-legal, historical-legal and dialectical methods are applied. The author founds out that despite the prohibition of biological weapon there are still other urgent issues such as an international control mechanism for monitoring the non-proliferation of biological weapons has not been established yet. The Protocol to the Biological and Toxin Weapons Convention (BTWC) has not been adopted yet. The study concludes with an idea that the problem of banning certain types of biomedical research has not been solved in some States and at the international level. In this paper, we interpret the concept of biosafety rather broadly, considering the issues typical of allied industries. Biosecurity and biosafety are directly related to ensuring environmental security, marine security, food security and outer space security. The researcher paid attention to the issue of legal regulation of ensuring environmental, biological, and food safety. Due to this fact, it is hard to do so with regard to the causal link between the acts (bioterrorism) of state agencies, the violation of the principles of international law, standards of human rights and the consequences that occurred. It is not clear from the text of the BTWC Convention which international organ/body can investigate such acts in international affairs and which norm of international law directly should be applied. Following a review of the content, the author raised possible problems, strategies, suggestions and guidelines for ensuring biosafety in international law. The author concluded that near future new categories of weapons of mass destruction appear in the world, moreover, genetic weapons should be classified as weapons of mass destruction, along with chemical, biological, bacteriological, and nuclear weapons. Technological developments will trigger the issues of fundamental principles in current international law. The author came to the conclusion about extension of the universal jurisdiction of the International Criminal Court in case biological and genetic weapons are used. The author encourages the complement to the international legal regulation the necessity to adopt a Protocol to the Biological and Toxin Weapons Convention (BTWC), establishing an international control mechanism for verifying prohibitions on the development, production, and stockpiling of biological weapons is obvious. The Convention on the Prohibition of the Development, Production and Stockpiling of Bacteriological (Biological) and Toxin Weapons and on their Destruction adopted in 1993, which contains a mechanism for verifying compliance with the prohibitions of the Convention, can be considered a precedent for the effective regulation of the circulation of hazardous substances all over the world. A pesquisa busca compreender o conteúdo e o conceito jurídico de biossegurança no Direito Internacional. Ao elencar as questões de biossegurança a fim de definir aspectos concretos relacionados à responsabilidade dos Estados pelo uso de armas biológicas analisa as novas tendências jurídicas para garantir a biossegurança internacional. O artigo levanta diversas questões sobre o que deve ser considerado uma guerra justa na perspectiva do Direito Internacional Humanitário, as questões dos princípios fundamentais do Direito Internacional atual (o princípio do uso da força, o direito dos Estados à legítima defesa em caso de bioataque, o princípio da solução pacífica de controvérsias internacionais, o princípio da não interferência nos assuntos internos dos Estados, o controle de armas e a responsabilidade). Ainda, apresenta uma visão geral de novos tipos de soberania, como biossoberania, soberania cibernética e soberania genômica dos Estados, o conceito jurídico de biocrimes internacionais (genocídio), a classificação jurídica do bioterrorismo, bioagressão, biopolítica e bioeconomia. Com isso, considera a importância de facilitar a interpretação ampla do conceito de biossegurança. A pesquisa utiliza técnicas científicas gerais e técnicas cognitivas especiais, nas quais são aplicados métodos de análise e síntese jurídica, sistêmicos, jurídico-formais, jurídico-comparativos, histórico-jurídicos e dialéticos. Assim, apesar da proibição de armas biológicas, ainda existem outras questões urgentes, como a criação de um mecanismo internacional de controle para monitorar a não proliferação de armas biológicas pois o Protocolo à Convenção sobre Armas Biológicas e Tóxicas (BTWC) ainda não foi adotado. O estudo conclui com a ideia de que o problema da proibição de certos tipos de pesquisa biomédica não foi resolvido em alguns Estados e em nível internacional. Neste artigo, interpreta-se o conceito de biossegurança de forma ampla, considerando as questões típicas das indústrias aliadas. Biossegurança e bioproteção estão diretamente relacionadas à garantia da segurança ambiental, segurança marítima, segurança alimentar e segurança do espaço sideral. O pesquisador se concentrou na questão da regulamentação legal para garantir a segurança ambiental, biológica e alimentar. Devido a esse fato, é difícil fazê-lo em relação ao nexo causal entre os atos (bioterrorismo) de agências estatais, a violação dos princípios do direito internacional, padrões de direitos humanos e as consequências ocorridas. Não fica claro no texto da Convenção BTWC qual órgão/organismo internacional pode investigar tais atos em assuntos internacionais e qual norma de direito internacional deve ser aplicada diretamente. Após uma revisão do conteúdo, o autor levantou possíveis problemas, estratégias, sugestões e diretrizes para garantir a biossegurança no direito internacional. Conclui-se que, em um futuro próximo, novas categorias de armas de destruição em massa surgirão no mundo; além disso, as armas genéticas devem ser classificadas como armas de destruição em massa, juntamente com armas químicas, biológicas, bacteriológicas e nucleares. Os desenvolvimentos tecnológicos desencadearão questões de princípios fundamentais no direito internacional atual. Com isso, conclui-se pela extensão da jurisdição universal do Tribunal Penal Internacional em caso de uso de armas biológicas e genéticas. A pesquisa incentiva a complementação da regulamentação jurídica internacional; a necessidade de adotar um Protocolo à Convenção sobre Armas Biológicas e Tóxicas (BTWC), que estabeleça um mecanismo de controle internacional para verificar as proibições ao desenvolvimento, produção e estocagem de armas biológicas, é óbvia. A Convenção sobre a Proibição do Desenvolvimento, Produção e Estocagem de Armas Bacteriológicas (Biológicas) e Tóxicas e sobre sua Destruição, adotada em 1993, que contém um mecanismo para verificar o cumprimento das proibições da Convenção, pode ser considerada um precedente para a regulamentação efetiva da circulação de substâncias perigosas em todo o mundo.